2013
DOI: 10.1088/1367-2630/15/12/123025
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of next-nearest-neighbor interlayer interaction in the magnetic behavior of magnetic/non-magnetic multilayers

Abstract: A striking multiple-step behavior has been observed in magnetoresistance measurements during magnetization reversal in anti-ferromagnetically coupled GaMnAs/GaAs:Be multilayers. This behavior arises from the splitting of the energy degeneracy of spin configurations established by nearest-neighbor interlayer exchange coupling (NN IEC) with contribution from the next-nearestneighbor (NNN) IEC. This observation reveals that NNN IEC plays a crucial role in the magnetic behavior of these multilayer structures.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
(60 reference statements)
2
12
0
Order By: Relevance
“…Notice further that the saturation magnetization was completed through a few transition steps. Such a multiple-step feature was previously observed in the magnetization reversal process of [GaMnAs/GaAs:Be] 10 multilayer systems and explained by the influence of the next nearest neighbor (NNN) IEC, which split the degenerated spin configurations that were formed by the NN IEC [12], [18]. The step feature in the MR, therefore, implies the presence of contribution from NNN IEC in our [GaMnAs/GaAs:Be] 6 multilayer systems.…”
Section: Methodssupporting
confidence: 68%
“…Notice further that the saturation magnetization was completed through a few transition steps. Such a multiple-step feature was previously observed in the magnetization reversal process of [GaMnAs/GaAs:Be] 10 multilayer systems and explained by the influence of the next nearest neighbor (NNN) IEC, which split the degenerated spin configurations that were formed by the NN IEC [12], [18]. The step feature in the MR, therefore, implies the presence of contribution from NNN IEC in our [GaMnAs/GaAs:Be] 6 multilayer systems.…”
Section: Methodssupporting
confidence: 68%
“…This was demonstrated experimentally in a magnetic semiconductor multilayer, where next-nearest neighbor interlayer exchange coupling was invoked to explain a sequential switching of the magnetic layers [25]. Furthermore, it has been shown in Fe/V superlattices that the dependence of the ordering temperature on number of bilayer repeats is not consistent with only nearest neighbor interactions [26].…”
Section: Discussionmentioning
confidence: 97%
“…12) In the course of such studies the signature of next-nearest-neighbor (NNN) IEC has been observed in [GaMnAs/GaAs:Be] 10 multilayers, showing a striking multiple-step GMR-like behavior during magnetization reversal. 13) Specifically, these studies showed that NNN IEC removes the degeneracy of NN IEC in the multilayers, such that each step appearing during the field sweep corresponds to a different alignment of GaMnAs magnetizations within the structure. The identification of spin configurations corresponding to each step then provides the opportunity for investigating the IEC acting on individual GaMnAs layers.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of spin configurations corresponding to each step then provides the opportunity for investigating the IEC acting on individual GaMnAs layers. 13) While the measurement in Ref. 13 have qualitatively established the presence of NNN IEC in the [GaMnAs/ GaAs:Be] 10 multilayers, the objective of this paper is obtain a quantitative determination of the magnitude of the IEC acting on each magnetic layer in the multilayer structure.…”
Section: Introductionmentioning
confidence: 99%